Prognostic role of platelet‐to‐lymphocyte ratio in oral cancer: A meta‐analysis. (26th February 2019) - Zhang, Yonggang; Zheng, Linli; Quan, Liuliu; Du, Liang
Abstract : Background and objective: Platelet‐to‐lymphocyte ratio (PLR) has been suggested to be associated with the progression of oral cancer with inconclusive results. The objective of the current study was to assess the prognostic role of oral cancer by meta‐analysis. Method: PubMed, EMbase(Ovid), CNKI, WanFang Data, VIP, and CBM databases were searched up to August 24, 2018. Studies investigating the association between PLR and progression of oral cancer were included. Meta‐analysis was performed by using Revman 5.3 software. The protocol of the study was registered on PROSPERO (CRD42018106836). Results: A total of five studies were included in the meta‐analysis. The results of the meta‐analysis showed that higher PLR was associated with the poor progress of oral cancer (overall survival: OR = 2.06, 95 CI: 1.49‐2.86, P < 0.0001; disease‐specific survival: OR = 2.12, 95 CI: 1.59‐2.82, P < 0.00001). Conclusion: The current meta‐analysis showed that higher PLR is a poor progression factor for oral cancer. However, larger sample, multi‐center studies should be carried out in the future to validate the above conclusion.